Insights into the percutaneous penetration of antidiabetic agents. (7th February 2017) - Ita, Kevin
Abstract: It has been suggested that destruction of β cells through apoptosis leads to type 1 diabetes (T1DM) while type 2 diabetes (T2DM) is caused mainly by increased insulin resistance. Several therapeutic agents are available for the management of diabetes. While researchers continue to investigate disease-modifying compounds, it is also important to develop alternative drug delivery systems for existing medications with the goal of modulating bioavailability and/or pharmacokinetic half-life. Transdermal drug delivery offers a number of advantages including improved compliance, lack of gastric irritation and the possibility of altering bioavailability and and/or half-life. In this review, the percutaneous penetration of antidiabetic agents is discussed. This is particularly significant given the fact that several compounds with hypoglycemic properties are being developed by academic research laboratories and the biotechnological industry. Microneedles, sonophoresis, chemical penetration enhancers and iontophoresis are some of the approaches used for the transdermal delivery of antidiabetic agents. It is anticipated that with more research, some of these transdermal drug delivery systems will be incorporated into clinical practice.